2023
DOI: 10.3389/fphar.2023.1194343
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ferroptosis, a novel programmed cell death, for the potential of alcohol-related liver disease therapy

Abstract: Ferroptosis is a new iron-dependent cell death mode, which is different from the other types of programmed cell death, such as apoptosis, necrosis, and autophagy. Ferroptosis is characterized by a process in which fatal lipids from lipid peroxidation accumulate in cells and eventually lead to cell death. Alcohol-related liver disease (ALD) is a type of liver injury caused by excessive alcohol intake. Alcohol-related liver disease is a broad-spectrum disease category, which includes fatty liver, steatohepatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 132 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…GPX4 is the only enzyme that reduces cholesterol, hydrogen peroxide and oxidized fatty acids. GPX4 can convert reduced GSH to oxidized glutathione and lipid hydrogen peroxide (L-H 2 O 2 , toxic) to lipid alcohols (L-OH, non-toxic), thereby promoting the decomposition of hydrogen peroxide and inhibiting ferroptosis ( 63 , 64 ). This indicated that reduced GPX4 activity favors ferroptosis ( 65 , 66 ).…”
Section: Ferroptosismentioning
confidence: 99%
“…GPX4 is the only enzyme that reduces cholesterol, hydrogen peroxide and oxidized fatty acids. GPX4 can convert reduced GSH to oxidized glutathione and lipid hydrogen peroxide (L-H 2 O 2 , toxic) to lipid alcohols (L-OH, non-toxic), thereby promoting the decomposition of hydrogen peroxide and inhibiting ferroptosis ( 63 , 64 ). This indicated that reduced GPX4 activity favors ferroptosis ( 65 , 66 ).…”
Section: Ferroptosismentioning
confidence: 99%
“…Alcohol-related liver disease (ALD), the leading global cause of chronic liver disease, involves pathological processes ranging from hepatic steatosis to inflammation, fibrosis, cirrhosis, and HCC [ 112 ]. Increasing evidence suggests that ferroptosis plays an important role in ALD and holds promise as an ideal target [ 113 ]. Alcohol promotes intestinal iron absorption and increases the risk of hepatic iron overload through a synergistic effect with free iron [ 113 ].…”
Section: Nac Treat Liver Disease By Targeting Ferroptosismentioning
confidence: 99%
“…Increasing evidence suggests that ferroptosis plays an important role in ALD and holds promise as an ideal target [ 113 ]. Alcohol promotes intestinal iron absorption and increases the risk of hepatic iron overload through a synergistic effect with free iron [ 113 ]. In addition, acetaldehyde, the major intermediate metabolite of ethanol, is responsible for the generation of ROS and down-regulating the expression of key antioxidant genes such as Nrf2 , thereby impairing the antioxidant system [ 114 ].…”
Section: Nac Treat Liver Disease By Targeting Ferroptosismentioning
confidence: 99%
“…GPX4 leverages the activity of a wide range of reductants to detoxify the oxidative radicals and is thus the main inhibitor of ferroptosis [ 3 , 33 , 34 ]. GSH is the major reducing substrate for GPX4.…”
Section: Regulation Of Ferroptosismentioning
confidence: 99%